2006
DOI: 10.1143/jjap.45.1226
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Multilayered Media Structure for Three-Dimensional Optical Memory

Abstract: We analyzed the optimum structure of recording media for a reflection confocal readout system of three-dimensional optical memory. In this analysis, we discuss the overlapping regions of the coherent transfer function of the reflection confocal readout system and the spatial frequency distribution of recorded bits. The intensity of the readout signal is proportional to the multiplication of the three-dimensional distribution of the coherent transfer function of the reflection confocal system and the spatial fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Several studies of laminate multilayer discs have been reported. 23,24) In these studies, recording and PSA layers were stacked alternately. Hence, there are interface reflections between the recording layer and the PSA layer on both sides of the recording layer.…”
Section: Principle Of Recording Layer Designmentioning
confidence: 99%
“…Several studies of laminate multilayer discs have been reported. 23,24) In these studies, recording and PSA layers were stacked alternately. Hence, there are interface reflections between the recording layer and the PSA layer on both sides of the recording layer.…”
Section: Principle Of Recording Layer Designmentioning
confidence: 99%
“…Therefore, multilayer disks and three-dimensional memories have been investigated to attain large data capacities. [1][2][3][4] A large space is required between recording layers in order to avoid interlayer crosstalk, and the optical absorption in each recording layer limits the number of layers. Therefore, a new record and retrieve system is required to fabricate 1 TB optical disks for data storage hierarchy requested by the Information and Communication Technology (ICT) Society.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] We have also developed a 3-D multilayered optical memory, in which photosensitive layers and transparent layers are piled up alternately. 9,10) Because we use pressure-sensitive adhesives (PSAs) as transparent layers, we can easily fabricate multilayered structures. We demonstrated recording and reading bit data in a multilayered medium that contains twenty recording layers.…”
Section: Introductionmentioning
confidence: 99%